Optimal Cooperation Strategy in Cognitive Radio Systems with Energy Harvesting - Yin, Sixing; Zhang, Erqing; Qu, Zhaowei; Yin, Liang; Li, Shufang (IEEE transactions on wireless communications, 2014)
In recent years, the excessive energy consumption in wireless communication systems has been increasingly critical, and environmental and financial considerations have motivated a trend in wireless communication technologies to resort to renewable energy sources. Energy harvesting is considered as a promising solution to alleviate such issues and has received extensive attentions. In this paper, we consider a cognitive radio system with one primary user (PU) and one secondary user (SU) and both of their transmitters operate in time-slotted mode. The SU, which harvests energy exclusively from ambient radio signal, follows a save-then-transmit protocol. In such a scenario, we investigate the SU's optimal cooperation strategy, namely, the optimal decision (to cooperate with the PU or not) and the optimal action (to spend how much time on energy harvesting and to allocate how much power for cooperative relay). We separately investigate the optimal action in non-cooperation and cooperation modes to maximize the SU's achievable throughout and derive the optimal closed-form solutions. Based on the analytical results of the optimal solutions, we propose the optimal cooperation protocol (OCP) to make the optimal decision, which simply involves a two-level test. Simulation results show that the proposed OCP outperforms the other two protocols (non-cooperation protocol and stochastic cooperation protocol) and the optimal underlay (OU) transmission mode.